Child Welfare Workers' Perceptions of Supervisory Support:A Curvilinear Interaction of Work Experience and Educational Background. Issue 3 (27th May 2018) - Kim, Jangmin; Park, Taekyung; Pierce, Barbara; Hall, James A.
ABSTRACT: This study draws on a developmental model of supervision to examine the effects of work experience and educational background on supervisory support perceived by child welfare workers. This study showed that the relationship between work experience and perceptions of supervisory support was curvilinear with a U -shaped curve. This study also found that unlike workers with non-social-work degrees, the perceived supervisory support of workers with social work degrees steadily increased but sharply decreased as work experience increased (inverted U -shaped curve). These findings suggest that supervisors should provide individualized supervision that matches the developmental needs of workers with different backgrounds.